Correction to: Determination of Reference Intervals of Biochemistry Parameters in healthy individuals in Gaziantep Province - Örkmez, Mustafa; Tarakçıoğlu, Mehmet (European Journal of Therapeutics, 2024)
In the first published version of this article [1], the authors stated that "Funding: The authors declare no funding" was misspelled. This has been changed to "Funding: The study was supported by Gaziantep University Scientific Research Projects Unit with project number TF.11.36". The authors take full responsibility for this confusion, and they apologize for the confusion. Publisher’s Note: The original article has been corrected, and a correction note was added. The original article can be find online at; https://doi.org/10.58600/eurjther.20232902-1343.y